EMPLOYEE ORGANIZATIONAL COMMITMENT IN LOCAL ADMINISTRATIVE ORGANIZATIONS IN PHROMGURI DISTRICT, SING BURI PROVINCE - Siriphornwut, Nattawat; Simakul, Surapron; Srisasalak, Charoen; Koson, Chawadee (Journal of MCU Nakhondhat, 2025)
This research aimed to 1) Examine the organizational commitment of employees in local administrative organizations in Phrombuuri District, Sing Buri Province, 2) Compare the organizational commitment of these employees based on individual demographic factors in Phromburi District, Sing Buri Province 3) Investigate the impact of job characteristics on organizational commitment, and 4) Analyze the influence of the work environment on organizational commitment in Phromburi District, Sing buri Province. The study employs a quantitative research design. The sample was the entire population of personnel of local government organizations in Phromburi District, 170 people. A questionnaires was used as the research instrument. Statistical analysis was conducted using frequency, percentage, mean, standard deviation, F-test, t-test, correlation coefficient analysis, and hypothesis testing through multiple regression analysis. The results revealed that 1) The level of organizational commitment among employees in local administrative organization personnel in Phromburi District was high 2) There were no significant no significant differences in organizational commitment, 3) Job characteristics had a positive and singnificant impact on organizational commitment at a high level, with an R Square value of .432 and 4) The work environment positively influenced organizational commitment at a high level, with an R Square value of .538.